Patogenisitas Streptokokus Grup B pada Mencit Neonatus - Zinatul HayatiO; Teuku Fadrial Karmil (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2009)
Group B Streptococci (GBS) are the major cause of serious infections in neonates, including pneumonia,septicemia and meningitis. Considering that GBS bacteria founded in Indonesia in our previous study isdissimilar as what have been found in foreign country particularly in its serotype distribution, thereforethis research is extremely essential to be conducted in Indonesia in order to searching the vaccine candidateto be used in Indonesia. This research focused in pathogenicity test of each GBS isolates on animal model.Pathogenicity experiment has been done by early onset septicemia model approach to neonatal mouse.Pathogenicity test result that SR-7 isolates can cause the death of neonatal mouse 100% in early-onsetinfection. Whereas, SV-2 isolates cannot cause the neonatal mouse neither in early-onset nor in late-onset.From the serotype determination result at previous research found that SR-7 isolates is serotype isolatesVI whilst SV-2 isolates is serotype III. This result has shown that SR-7 (serotype VI) isolates is the mostpathogen and the SV-2 isolates is less pathogen.